Kyslíkové řezání vysokopevnostních ocelí - Lupták, Jakub (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2024)
Práca sa venuje problematike tepelného delenia a jeho využitia pre vysokopevnostné oceli. Pre delenie týchto materiálov je najčastejšie používané plazmové rezanie a táto práca skúma alternatívnu možnosť rezania kyslíkom. V teoretickej časti sú pojednávané vysokopevnostné oceli, možnosti ich tepelného delenia, zvolenie metód pre praktickú časť a ich princíp fungovania. V experimentálnej časti je prevedené rezanie vybraných VP ocelí kyslíkom a plazmou pri dvoch rezných rýchlostiach. Na odrezaných vzorkách bola ďalej skúmaná zmena tvrdosti na reznej hrane a veľkosť tepelne ovplyvnenej oblasti od technológií. Na koniec bola posúdená vhodnosť kyslíkovej technológie pre rezanie vysokopevnostných ocelí.

The work focuses on the issue of thermal cutting and its use for high-strength steels. Plasma cutting is most commonly used for cutting these materials, and this work explores the alternative possibility of cutting with oxygen. The theoretical part discusses high-strength steels, the possibilities of their thermal cutting, the selection of methods for the practical part, and their principles of operation. Specific methods for the experimental part are selected and detailed in terms of their principles of operation. The experimental part involves cutting selected samples of high-strength steels using oxygen and plasma at two different cutting speeds. Changes in hardness at the cutting edge are analyzed, and the size of the heat-affected zone for both technologies is evaluated. Finally, the suitability of oxygen cutting technology for high-strength steels is assessed.
Oxigen cutting of high strength steels
Keywords: vysokopevnostná oceľ; kyslíkové rezanie; plazmové rezanie; tvrdosť; tepelne ovplyvnená oblasť; high strength steel; oxygen cutting; plasma cutting; hardness; heat affected zone